1997
DOI: 10.1091/mbc.8.8.1461
|View full text |Cite
|
Sign up to set email alerts
|

The spindle pole body of Schizosaccharomyces pombe enters and leaves the nuclear envelope as the cell cycle proceeds.

Abstract: The cycle of spindle pole body (SPB) duplication, differentiation, and segregation in Schizosaccharomyces pombe is different from that in some other yeasts. Like the centrosome of vertebrate cells, the SPB of S. pombe spends most of interphase in the cytoplasm, immediately next to the nuclear envelope. Some y-tubulin is localized on the SPB, suggesting that it plays a role in the organization of interphase microtubules (MTs), and serial sections demonstrate that some interphase MTs end on or very near to the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
269
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(281 citation statements)
references
References 44 publications
10
269
2
Order By: Relevance
“…The ratio of cells with and without spots was similar to the ratio of interphase and mitotic cells in a log phase culture of fission yeast (Mitchison and Nurse, 1985). The predominance of two spots versus one spot is consistent with the association of unseparated and separated mitotic SPBs within the nuclear envelope (Ding et al, 1997). Therefore, the bright spot(s) were interpreted as mitotic spindle pole bodies.…”
supporting
confidence: 70%
See 3 more Smart Citations
“…The ratio of cells with and without spots was similar to the ratio of interphase and mitotic cells in a log phase culture of fission yeast (Mitchison and Nurse, 1985). The predominance of two spots versus one spot is consistent with the association of unseparated and separated mitotic SPBs within the nuclear envelope (Ding et al, 1997). Therefore, the bright spot(s) were interpreted as mitotic spindle pole bodies.…”
supporting
confidence: 70%
“…The mitotic stages described for images in Figure 9 are inferred from the configuration of the SPBs and the nuclear envelope at specific times as previously reported (Ding et al, 1993(Ding et al, , 1997. These stages of mitosis correspond to the time when the SPB is anchored in the nuclear envelope (Ding et al, 1997).Cut11p has the same localization pattern in meiotic cells as that described for vegetative growth. cut11: GFP cells of the opposite mating type were induced to mate by starving for nitrogen on malt agar plates (Moreno et al, 1991) and were observed at various stages of the meiotic life cycle.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…It is widely known that such shape evolution is driven by the poleward force generated by kinesins along with other microtubule-associated proteins that reside at the overlapping region of antiparallel spindle microtubules (MTs) nucleated from the two spindle pole bodies (SPBs) at both ends of a dividing nucleus (5)(6)(7)(8). Throughout interphase, there is only one SPB in the cytoplasm that starts to duplicate in G1/S phase, resulting in two SPBs embedded in the NE during mitosis (9). Besides generating forces, spindle MTs are also responsible for moving sister chromatids toward the opposite poles through capturing the kinetochore, a large proteinaceous complex on chromosomes (10).…”
Section: Introductionmentioning
confidence: 99%